Dramatization, Online Learning, Character: Navigating the Formation of Anti-Radicalism in Higher Education - Mohammad Rindu Fajar Islamy; Ahmad Fuadin; Miftahul Ulum; Restu Adi Nugraha; Kamaludin Kamaludin; Haerudin Haerudin (Higher Education Spiritual Pedagogies, 2023)
This case study-based research aims to examine the concept of dramatization in religious learning as a bridge in increasing students' character formation and tolerance in the dimensions of globalization and modernity. According to the concept initiated by Nunez and Navaro, dramatization can create a space where value education can be developed, which is usually challenging to achieve in an educational context. Contemporary scientists consider dramatization as a source of pedagogical effectiveness in internalizing various attitudes, positions, reasoning, and thoughts to promote a culture of peace. This research method uses qualitative, with a case study of online religious learning by lecturers at one of the tertiary institutions in Bandung. This research was built in two stages: 1) a literature study and 2) interviews with informants. The number of informants who participated in this research was 15 students, and then we analyzed the data using the theoretical approach of Miles and Huberman. The results of the study show several urgent findings, including; 1) Dramatization of learning contributes significantly to increasing individual piety, tolerance, and cognitive aspects, 2) the success of learning dramatization is built on three fundamental processes that are interconnected, namely 1) Pre-Learning, 2) Learning Process, and 3) Post-Learning.